(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2025)
By distinguishing between the age before art and the age of art, recent studies have reinforced the idea of art as a distinctly modern phenomenon. Prior to the advent of art, what we now consider artworks were primarily sacred objects, whose ontological status was fully realized in acts of worship. From this historical reconstruction arises the hypothesis that the artwork emerged through the secularization of the sacred object, wherein its sacredness was replaced by aesthetic value. In this essay, we aim to demonstrate that both the sacred object and the artwork originate from the use of the frame as a device of meaning. When a framed space is believed to be linked to supernatural forces, the frame designates a sacred space (or object). Conversely, when the frame encloses a profane world distinct from the external one - yet capable of offering a deeper understanding of it - the frame defines an artwork.